2022
DOI: 10.3389/fphar.2022.1071365
|View full text |Cite
|
Sign up to set email alerts
|

Identification of super-enhancer-driven peptidyl arginine deiminases as potential biomarkers and therapeutic targets for osimertinib-resistant non-small cell lung cancer

Abstract: Resistance to targeted drugs is now a challenging clinical problem in the treatment of non-small cell lung cancer (NSCLC). So far, there are no approved targeted therapeutic drugs for patients with disease progression after the third-generation epidermal growth factor receptor-tyrosine kinase inhibitor osimertinib resistance (OR). Super-enhancers (SEs) are large clusters of transcriptional enhancers that drive gene expression. In this study, we aimed to explore the potential pathogenic SEs and their driven gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…On the other hand, gain of function experiments carried out by overexpressing PADI3 in BT474 cells resulted in resistance to the antitumoral action of neratinib, supporting the concept that increased levels of PADI3 may provoke resistance to the drug. Other authors have demonstrated resensitization of NSCLC cells to osimertinib, a TKI against EGFR, after inhibiting PADI1, 2 and 3 with Cl-amidine (27). However, we are not aware of any studies that have demonstrated the involvement of these enzymes in the acquisition of resistance to any drug used in the therapy of HER2 + breast cancer.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…On the other hand, gain of function experiments carried out by overexpressing PADI3 in BT474 cells resulted in resistance to the antitumoral action of neratinib, supporting the concept that increased levels of PADI3 may provoke resistance to the drug. Other authors have demonstrated resensitization of NSCLC cells to osimertinib, a TKI against EGFR, after inhibiting PADI1, 2 and 3 with Cl-amidine (27). However, we are not aware of any studies that have demonstrated the involvement of these enzymes in the acquisition of resistance to any drug used in the therapy of HER2 + breast cancer.…”
Section: Discussionmentioning
confidence: 85%
“…Peptidylarginine deiminases (PADs) are a group of calcium-dependent enzymes that catalyze the post-translational conversion of arginine to citrulline, leading to changes in protein structure and function (22)(23)(24). Several studies have already demonstrated their involvement in the process of tumorigenesis or tumor progression (25)(26)(27). The 5 family members (PADI1, 2, 3, 4 and 6) have distinct substrate a nities and tissue-speci c expression patterns (28).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation